Evaluating Differential Item Functioning in the English General Practice Patient Survey: Comparison of South Asian and White British Subgroups. Issue 9 (September 2015) - Setodji, Claude M.; Elliott, Marc N.; Abel, Gary; Burt, Jenni; Roland, Martin; Campbell, John
Abstract : Objective: To evaluate two 5-item patient experience scales from the English General Practice (GP) Patient Survey for evidence of differential item functioning (DIF) given prior evidence of substantially worse reported health care experiences for South Asian compared with white British respondents. Setting: A national survey of English patients' primary care experiences. Method: We used classic test and item response theory analysis to examine the possibility of DIF by patient ethnicity (South Asian, white British) after controlling for age, sex, health status, and quality of life in the English GP Patient Survey conducted in 2011/2012. Results: Data were available for 873, 051 respondents (818, 219 white British/54, 832 South Asian from 7795 English practices) who answered items relating to experiences of GP or nurses' care. Internal consistency reliability was high and similar for South Asian and white British patients. White British patients reported better average experiences than South Asians, but there was no evidence of DIF or different item response curves for white British and South Asian respondents, even in sensitivity analyses using matched samples. Conclusions: All communication items in the English GP Patient Survey showed similar South Asian versus white British differences, with no evidence of DIF. In contrast, differences due to scale use or expectations are typically variable rather than constant across scales. While other possibilities remain, these findings increase the likelihood that the observed negative responses of South Asian patients to this national survey reflect true differences in their experiences of care. Abstract : Supplemental Digital Content is available in the text.